THE USE OF FACEBOOK GROUP AS A MEDIA TO TEACH TENTH GRADERS’ READING COMPREHENSION OF NARRATIVE TEXT IN SMAN 2 SIDOARJO (RETAIN, 2017)
THE USE OF FACEBOOK GROUP AS A MEDIA TO TEACH TENTH GRADERS’ READING COMPREHENSION OF NARRATIVE TEXT IN SMAN 2 SIDOARJO Aprilia Eka Sasanti English Education Department, Language and Arts Faculty, Surabaya State University Email: apriliaekasasanti@unesa.ac.id Dr. Oikurema Purwati, M.Appl English Education Department, Language and Arts Faculty, Surabaya State University Email: oikuremapurwati@unesa.ac.id Abstract Since Reading is considered to be a boring activity, it is necessary that teachers choose an appropriate media to attract the students improve their reading comprehension. One of the media which can used to attract the students is Facebook Group. Facebook is one of the social media that is easier and pleasing to be used to teach EFL learners. This research was done as a way to find out whether students who are taught by using Facebook Group get better understanding narrative text compared by the students who are not. It has experimental research design, the samples are 36 students of X MIA 1 as an experimental group and 36 students of X MIA 2 as a controlled group. In addition, the data are the scores of the participants’ post-test which are analyzed using Independent samples T-test. The result shows that the reading comprehension of Narrative text of the students is better than the controlled group after being taught using Facebook Group. Keyword: Facebook Group, Reading, Narrative Text Abstrak Reading adalah salah satu kegiatan yang membosankan, oleh karena itu guru diharapkan memilih media yang tepat untuk mengesankan siswa meningkatkan pemahaman membaca mereka. Salah satu media yang dapat digunakan untuk menarik siswa adalah Facebook Group. Facebook group merupakan salah satu media sosial yang lebih mudah dan menyenangkan untuk digunakan untuk mengajar murid-murid EFL. Penelitian ini dilakukan sebagai cara untuk mengetahui apakah siswa yang diajar dengan menggunakan Facebook Group mendapatkan teks naratif pemahaman yang lebih baik dibandingkan dengan siswa yang tidak. Ini memiliki desain penelitian eksperimental, sampel adalah 36 siswa dari X MIA 1 sebagai kelompok eksperimen dan 36 siswa dari X MIA 2 sebagai kelompok kontrol. Selain itu, data skor pasca tes peserta yang dianalisis menggunakan sampel Independent T-test. Hasil penelitian menunjukkan bahwa pemahaman membaca Narasi teks siswa lebih baik daripada kelompok kontrol setelah diajarkan menggunakan Facebook Group. Kata Kunci: Grup Facebook, Membaca, Teks Narrative.